Alternative Methods to Treat Nausea and Vomiting from Cancer Chemotherapy. (8th November 2015) - Sheikhi, Mohammad Ali; Ebadi, Ahmad; Talaeizadeh, Abdolhassan; Rahmani, Hossein
Abstract : Chemotherapy Induced Nausea and Vomiting (CINV) is among the most intensive side effects and critical concerns for patients with cancer. Most of these patients experience nausea and vomiting after chemotherapy. Sometimes, this is so annoying that it may prevent them from continuing the therapy. With the recent advances, a variety of therapeutic methods are innovated and applied to control CINV. Among them, the main methods include medicinal therapy, relaxation, and herbal therapy. Yet, using dexamethasone together with massage therapy and ginger is identified as the most effective method.